You would take d times t seconds and find the answer
Answer:
216 cm^2
Step-by-step explanation:
A cube has 6 congruent, square faces.
Each face has side length of 6 cm.
The total surface area is the sum of the surface areas of the 6 faces, but since all faces are congruent, the total surface area is
SA = 6s^2
where s = side length
SA = 6 * (6 cm)^2
SA = 6 * 36 cm^2
SA = 216 cm^2
Idk really I enjoyed this mathematics
In this case, we'll have to carry out several steps to find the solution.
Step 01:
Data
f(x) = √3x
g(x) = √48x
(f . g)(x) = ?
Step 02:
(f . g)(x) :
![\text{ (f.g)(x) = }\sqrt[]{3(\sqrt[]{48x)}}](https://tex.z-dn.net/?f=%5Ctext%7B%20%20%20%20%20%20%20%20%20%20%28f.g%29%28x%29%20%3D%20%7D%5Csqrt%5B%5D%7B3%28%5Csqrt%5B%5D%7B48x%29%7D%7D)
![(f.g)(x)\text{ = }\sqrt[]{3(48x)^{\frac{1}{2}}}\text{ }](https://tex.z-dn.net/?f=%28f.g%29%28x%29%5Ctext%7B%20%3D%20%7D%5Csqrt%5B%5D%7B3%2848x%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%7D%5Ctext%7B%20%7D)
(f.g)(x) = 12 √ x
The answer is:
(f.g)(x) = 12 √ x
Answer:
x>−6,x<−12
Step-by-step explanation:
Break down the problem into these 2 equations.
x+9>3x+9>3
-(x+9)>3−(x+9)>3
Solve the 1st equation: x+9>3x+9>3.
x>-6x>−6
3 Solve the 2nd equation: -(x+9)>3−(x+9)>3.
x<-12x<−12
Collect all solutions.
x>-6,x<-12x>−6,x<−12